Compliment Responses by Iban ESL Learners / Christine Jacqueline Runggol - Runggol, Christine Jacqueline (UiTM Cawangan Johor, 2019)
The speech act of complimenting and how speakers give and respond to compliments have been much researched. This study attempts to investigate one major source of pragmatic misunderstanding among learners of English in Malaysia, specifically the different responses to compliments produced by a sample of Iban speakers of English in Sarawak. It also aims to classify response types according to pre-existing taxonomy and discuss any significant issues and implications for the teaching of English. The study was timely in the sense that there is currently a lack of data regarding the production of the speech act of complimenting and its elicited responses among the Iban community when they interact in English. The method used for this study was a Discourse Completion Test (DCT). The study revealed that the respondents generally accept the compliments given when complimented in both English and Iban. By accepting and giving positive elaboration, it can be said that the respondents are influenced culturally by the English language to a certain degree. The results of this study have provided some implications for the teaching of English as a second language in Malaysia. In order to produce students who are competent in the language, teachers must not only concentrate on the grammatical aspect of language teaching. Instead, they must also produce students who are aware of certain pragmatic rules of the L2 speech community in order to avoid communication breakdown.